Synthesis and Characterization of Silica from Lapindo Mud Waste with Acid and Base Solvents - Riesnawa, Yurdien Dellan; Azaria, Atha Nur; Reva Edra Nugraha (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Lapindo mud is a geological waste product resulting from the mud eruption in Sidoarjo, East Java, Indonesia, which continues to raise environmental concerns. However, this material has considerable potential due to its high silica (SiO2) content. This study evaluates the effectiveness of acid leaching and alkaline precipitation methods for extracting silica from Lapindo mud and investigates the properties of the resulting silica. Acid leaching was conducted using HCl (4, 8, and 10 M), while alkaline treatment employed NaOH (2, 6, 8, 10, and 12 M) and KOH (8, 10, and 12 M). The results showed that acid leaching is effective in removing metallic impurities without dissolving the silica framework, resulting in only a limited increase in SiO2 content from 54% to 57%. On other hand, silica purity was greatly increased by precipitation using a base solvent; the maximum SiO2 content was achieved at 97.5% with 10M NaOH. Nitrogen adsorption-desorption analysis shows that the precipitated silica had mesoporous properties with a type IV isotherm and an average pore size of 20.60 nm, while XRD analysis verifies the conversion of crystalline silica into amorphous silica. Thus, the most efficient technique for generating high-quality silica from Lapindo mud waste is alkaline precipitation with 10M NaOH